3 SUSPECTED MYCOBACTERIUM AVIUM-INTRACELLULARE AS AN ACUTE CAUSE OF PANCREATITIS IN PATIENT WITH ACQUIRED IMMUNODEFICIENCY SYNDROME. (10th December 2015) - Vergara, G.; Persing, B.; Nicholas, W.; Finley, R.
Abstract : Mycobacterium avium-intracellulare (MAC) has been associated with severe systemic disease in acquired immunodeficiency syndrome (AIDS) patients. However, MAC associated pancreatitis is rare with only a few documented case reports. 38 year-old black male with advanced AIDS (on highly active anti-retroviral therapy [HAART]), hepatitis C, crytococcal meningitis, and hypertension presented complaining of nausea, vomiting, and anorexia. Initially symptoms were felt to be secondary to cryptococcal meningitis; however, symptoms did not improve despite decreasing crytococcal titers. Subsequent laboratory evaluation revealed pancreatitis. HAART was held given risk of associated pancreatitis. Additional causes such as dyslipidemia, alcohol, and cholestatic disease were ruled out. Given failure to identify a cause, CT of chest, abdomen, pelvis revealed no significant underlying hepatic or pancreatic findings; however, extensive 1-2 cm mediastinal, mesenteric and retroperitoneal lymphadenopathy was noted. An excisional biopsy of the retroperitoneal lymph nodes was performed and was consistent with MAC infection. The patient was treated for MAC with sustained improvement of his symptoms as well as his serum pancreatic enzymes. Although there was lack of direct evidence of MAC as a cause for his pancreatitis, the clinical response is highly suggestive of this etiology. At this time no other etiologies have been implicated as his cause for pancreatitis. Discussion: Patients with HIV/AIDS are prone to develop multiple GI complications. These include chronic and acute diarrhea, non-specific abdominal pain, liver disease, GI bleeding, neoplasms, and pancreatitis. The causes of pancreatitis in HIV/AIDS patients include, but are not limited to, direct viral infections (primary HIV, CMV, HSV), fungi (Cryptococcus), bacteria (mycobacteriae), protozoa (Toxoplasma gondii), neoplasms (KS and NHL), drug induced (pentamidine, dideoxyinosine as the most common ones), as well as other common causes of pancreatitis. Opportunistic infections are not often considered in the initial evaluation of patients with HIV/AIDS who present with pancreatitis. While uncommon they should be considered since these are treatable/curable causes of pancreatitis.